Answer:
(a)
![f(a+h)=a^(2) +2ah+h^(2) -3a-3h-4](https://img.qammunity.org/2020/formulas/mathematics/college/yet68x7an7jv8q2tan0151jaxa1vmzx68y.png)
(b)
![f(a+h)-f(a)=2ah+h^(2) -3h](https://img.qammunity.org/2020/formulas/mathematics/college/8pv5tf0we3ger8gxx2lwa2gtwebtk8zc5b.png)
(c)
![(df(a+h))/(dx) \left \{ { \atop {a=7}} \right. =2h+11](https://img.qammunity.org/2020/formulas/mathematics/college/omil39x15npmxrgeswmtagi82cibh7z5tc.png)
Explanation:
(a)
Simply evaluate (a+h) in the function:
![f(a+h)=(a+h)^(2) -3(a+h)-4=a^(2) +2ah+h^(2) -3a-3h-4](https://img.qammunity.org/2020/formulas/mathematics/college/w2tmsqddlsvti9r098wdeylmdcbo5qqfc9.png)
(b)
Evaluate (a) in the function:
![f(a)=a^(2) -3a-4](https://img.qammunity.org/2020/formulas/mathematics/college/8ky47ae9ycl4umi3txiamhwvqlt07fsw2q.png)
Using the previous answers lets calculate f(a+h)-f(a)
![f(a+h)-f(a)=a^(2) +2ah+h^(2) -3a-3h-4-(a^(2) -3a-4)=2ah+h^(2) -3h](https://img.qammunity.org/2020/formulas/mathematics/college/uyax63d572ovjdii6ugnx5d06867uu1q08.png)
(c) To find the rate of change of f(a+1) when a=7 we need to calculate its derivate at that point:
![(df(a+h))/(dx) \left \{ { \atop {a=7}} \right. =2a+2h-3=2(7)+2h-3=2h+14-3=2h+11](https://img.qammunity.org/2020/formulas/mathematics/college/6n26tllm5byeik559mj5gn7jvtp8yeck5n.png)